2020
DOI: 10.21203/rs.2.23093/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Differentially Expressed microRNAs in Metastatic Ovarian Cancer

Abstract: Background: The molecular mechanisms of ovarian cancer (OC) remain unclear. We sought to comprehensively identify miRNAs that are aberrantly expressed in OC. Methods: Differentially expressed miRNAs were screened from six pairs of primary and metastatic OC tissues; their possible functions were then analyzed and target genes were predicted by bioinformatics. Then gene expression profiling results were established by reverse transcription quantitative polymerase chain reaction and western blot. Target binding b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…As intrinsic regulators, miRNAs have been shown to play critical roles in chondrocyte proliferation, differentiation, and endochondral ossification 16‐19 . In addition, aberrant miRNA expression is involved in many bone‐related disorders, including osteoarthritis, osteoporosis, and bone tumors 20‐22 . To the best of our knowledge, the role of miRNAs in the endochondral ossification of the acetabular roof has not yet been analyzed in the DDH setting.…”
Section: Introductionmentioning
confidence: 99%
“…As intrinsic regulators, miRNAs have been shown to play critical roles in chondrocyte proliferation, differentiation, and endochondral ossification 16‐19 . In addition, aberrant miRNA expression is involved in many bone‐related disorders, including osteoarthritis, osteoporosis, and bone tumors 20‐22 . To the best of our knowledge, the role of miRNAs in the endochondral ossification of the acetabular roof has not yet been analyzed in the DDH setting.…”
Section: Introductionmentioning
confidence: 99%
“…Our experiment investigated the ability of miR-210 stem cells to differentiate into chondrogenic and adipogenic lineages. Many studies have demonstrated that miR-210 promotes osteogenic differentiation of stem cells [22][23][24][25]. Notably, the results of Li et al [22] demonstrated that miR-210 promoted osteogenic differentiation of rat bone marrow stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐324‐5p is increased in end‐stage osteoarthritis by regulating hedgehog signaling and osteogenesis in human MSCs ( 53 ) and it is also downregulated in the bone marrow of osteoporotic patients. ( 54 ) By searching in the miRWalk database, we have found that miR‐324‐5p targets three genes (FOXO1/FOXO3, FOSB, and RUNX2) that promote osteoblastogenesis and consequently would interfere negatively with osteoblast differentiation and bone mineralization. Karvande and colleagues ( 55 ) have shown that the bone formation induced by PTH therapy was related to the increase in miR‐451a serum levels.…”
Section: Discussionmentioning
confidence: 99%